2015
DOI: 10.1111/mec.13287
|View full text |Cite
|
Sign up to set email alerts
|

Interclonal proteomic responses to predator exposure in Daphnia magna may depend on predator composition of habitats

Abstract: Phenotypic plasticity, the ability of one genotype to express different phenotypes in response to changing environmental conditions, is one of the most common phenomena characterizing the living world and is not only relevant for the ecology but also for the evolution of species. Daphnia, the water flea, is a textbook example for predator-induced phenotypic plastic defences; however, the analysis of molecular mechanisms underlying these inducible defences is still in its early stages. We exposed Daphnia magna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 90 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…Despite a sensible explanation for this observation as being linked to an increase in translation, previous studies have shown increased transcription of ribosomal proteins without increased production of ribosomes (Sun, Li, & Wang, ; Wang et al., ). Proteomic data gathered on D. magna in response to predator cues show similar, but less extreme responses in ribosomal protein up‐regulation (Otte, Schrank, Frohlich, Arnold, & Laforsch, ). Furthermore, it is known that ribosomal proteins have functions outside of ribosome assembly and translation in response to stress (i.e., oncoprotein suppression, immune signalling and development; Zhou, Liao, Liao, Liao, & Lu, ).…”
Section: Discussionmentioning
confidence: 97%
“…Despite a sensible explanation for this observation as being linked to an increase in translation, previous studies have shown increased transcription of ribosomal proteins without increased production of ribosomes (Sun, Li, & Wang, ; Wang et al., ). Proteomic data gathered on D. magna in response to predator cues show similar, but less extreme responses in ribosomal protein up‐regulation (Otte, Schrank, Frohlich, Arnold, & Laforsch, ). Furthermore, it is known that ribosomal proteins have functions outside of ribosome assembly and translation in response to stress (i.e., oncoprotein suppression, immune signalling and development; Zhou, Liao, Liao, Liao, & Lu, ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, many organisms express antipredator traits at the beginning of independent life, for example, as hatchlings, neonates, and seedlings (Osborn and Jaffe 1998;Laforsch and Tollrian 2004;Bosak et al 2013;Garla et al 2015). The expression of such traits can vary across genotypes prior to any exposure to cues from predators, and genotypes can differ with respect to the plasticity of those traits in response to cues from predators (Fischer et al 2014b;Sjoqvist et al 2014;Otte et al 2015;Christjani et al 2016). However, when animals are exposed to cues from predators, changes in antipredator behavior typically occur more rapidly than changes in morphological antipredator defenses (Van Buskirk 2002;Hossie and Murray 2012;Orizaola et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since Daphnia need to shed their rigid carapace in order to grow, molting is directly related to changes in body size. Another analysis of D. magna exposed to Triops cancriformis kairomones revealed the role of proteins related to the cuticle, muscular system, energy metabolism and regulatory proteins that may be involved in morphological carapace defenses and changes in resource allocation (Otte et al 2014). In conclusion, a number of biological functions hypothesized to be involved in kairomone response could be confirmed, e.g., transcripts related to body remodeling and growth.…”
Section: Discussionmentioning
confidence: 79%
“…The 'structural constituent of cuticle' was enriched in D. pulex exposed to Chaoborus kairomones Rozenberg et al 2015) and related to remodeling of the cuticle. Furthermore, it was also enriched in the proteomic response of D. magna to Triops cancriformis (Otte et al 2015) and is thought to be related to changes in carapace morphology as well as the formation of ultrastructural defenses of the cuticle (Rabus et al 2013). Genes related to body remodeling and activation of cuticle proteins were enriched for D. magna exposed to vertebrate and invertebrate predator kairomones (Orsini et al 2018).…”
Section: Discussionmentioning
confidence: 99%